Snowy Laundry / Myedzatul Noradeela Azdi... [et al.] - Azdi, Myedzatul Noradeela; Lamit, Nadhira; Halim, Nur Afieza; Sumadi, Siti Nor Sakilah (2011)
Our company’s name is Snowy Laundry and we are provided laundry services to all students that are studying in UiTM Sabah. Our business location is at Blok A2, Kolej Kediaman Kluster A, UiTM Sabah, Beg Berkunci 71, 88997, Kota Kinabalu, Sabah. We form a partnership business for this laundry service and have a task and responsibility on their own position whereby General Manager and the Administration Manager is Myedzatul Noradeela Binti Azdi, Marketing Manager is Nadhira Binti Lamit, Operation Manager is Nur Afieza Binti Halim and Financial Manager is Siti Nor Sakilah Binti Sumadi. Each of this position was very important to ensure the business objective, vision and mission can be achieved. In this partnership business we already make an agreement which is agreed by every member and this agreement is to prevent from any problem occur in future. Apart from that, we also have an incentive scheme for employee to encourage them to more responsible and have a high commitment in carrying their job. We had given incentive scheme like salary, employee’s provident fund (EPF), Social Security Organization (SOCSO), sick leave, bonus, and maternity leave. Other than that, we also have contribution among our members in term of cash, office equipment and fixed asset. Our cash contribution is RM20, 000 per partner. Besides that, we make a proper plan for each department to ensure the business objective can be achieved. Marketing plan involve the size market of the business, competitor, target market, strategies to promoting business and so on. The proper marketing plans know the best strategies to promote the business and also know how to compete with the other competitor. The strategy that we made to promote our business is through banner, signboard and also brochure. Furthermore, we also made a proper operation plan. Operation plan includes operation process planning, material planning, location planning and so on. Overall function of the operation plan is to ensure that the sources can be allocating in an effective and efficient way to prevent wastage of the resources and loss of production. In addition, choosing a strategic location planning is very important decision to make, because once the operation decided, it cannot be change and involve a lot of cost. Moreover, we also ensure that we make a proper financial planning. Through the financial planning we can determine the development and achievement of the business that we had planned. Financial will involve all of the cost needed from each department, such as administration budget, marketing budget and also the operational budget. All the data are very important to prepare financial projections for the current time and also in future. It is to provide a clear estimation of amount of money that needed to start and run a business. Therefore, each department perform an important task and responsibility in order to complete the business goals and the General Manager also have the most responsibility to planning, organizing, leading and controlling all the activities and employee to ensure that the business can run smoothly. Our laundry will provide the best laundry services to our customers and customer satisfaction is our priority.